(untitled) (LACCEI, 2024)
Be it due to time constraints or insufficient processing power – or a combination of both – the use of models with large numbers of Degrees of Freedom (DoF) may be unsuitable to provide a client with results in a timely manner. The use of physics-based reduced models – or proxy structures – are popular among practitioners to solve this issue, as they keep intact all the underlying properties of the 2nd Order Problem at a fraction of the cost. In this report, Interpolatory Methods of Model Reduction are explored as an alternative, and applied to a 3D Space Frame. The methods chosen allow for structure-preserving reduced models, and differ mainly on the selection of interpolation points. A comparison between the response of these reduced models and a proxy structure against two different types of inputs show that Interpolatory Methods are a viable, more flexible option when it comes to reducing the internal DoFs of a structural model, though engineering judgement is required to ensure it adequately captures the most relevant aspects of the response for the specific application.